Doença de lesões mínimas : a propósito de um caso clínico - Araújo, Maria Teresa Reis (2014)
Minimal change disease (MCD) is responsible from 10 to 15 % of cases of nephrotic syndrome in adults. The treatment of MCD in adults is challenging for three reasons: there is a lack of clinical trials in adults, the data are extrapolated from the pediatric cases; the pathophysiology of the disease remains unknown; the response to treatment and clinical course of the disease vary widely from patient to patient. The standard treatment through the use of corticosteroids leads to a complete remission in 80% of the cases, being the initial response to steroids the most important prognostic factor. Regarding the response to treatment, MCD is the kind of disease of "all or nothing", being the partial responses less usual. The presence of less than 10% of patients corticoresistance is defined by the lack of response after 16 weeks of adequate corticotherapy. Cyclosporine is the treatment suggested in corticoresistance, being this the selected option in the case presented.